Cattle grazing effects on mountain gazelles in Mediterranean natural landscapes. Issue 8 (22nd August 2017) - Shamoon, Hila; Dayan, Tamar; Saltz, David
ABSTRACT: Frequently, Mediterranean natural and semi‐natural areas will undergo cattle grazing as a form of fire fuel reduction management. We used a multi‐species approach to understand effects of cattle grazing on mountain gazelle ( Gazella gazella ) in relation to 2 potential predators of gazelle neonates: golden jackal ( Canis aureus ) and wild boar ( Sus scrofa ). We used light detection and ranging (LiDAR) data and a fine‐scale camera trap design (0.01‐km 2 grid) in Ramat Hanadiv Nature Park in the Mediterranean region of Israel to determine gazelle habitat and patch preferences in response to grazing using N‐mixture models. Cattle grazing decreased female gazelle detectability and activity and attracted potential predators during the most sensitive time of the year for gazelle: parturition and the critical first 5 weeks of fawns' lives. Grazing management acts as a disturbance for gazelles and increases risk for neonates. Our results show the importance of understanding the broader mechanism behind predator–prey dynamics and how indirect human‐mediated management actions and direct predation may have adverse effects on wild populations. We recommend that cattle be allowed to enter natural areas only after the spring birth peak. © 2017 The Wildlife Society. Abstract : Cattle grazing acts as a disturbance for mountain gazelles and increases risk for neonates. The results show the importance of understanding the broader mechanism behind predator–prey dynamics and how indirect human‐mediated management actions and direct predation can have adverse effects on wild populations.